1995
DOI: 10.1002/j.1550-8528.1995.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Drug Treatment of Obesity

Abstract: LUTES. Combined drug treatmet of obesity. Obes Res.Pharmacologicaltreatment of obesity has beenneglected as aviable therapeuticoption formany years. Recent long term studies with combinations of obesity drugs gives promise that drugs may play a role in weight maintenance, which classically has been the most difficult aspect of treating obesity. Currently available obesity drugs include centrally acting adrenergic agents and serotonin agonists. Drugs stillin development include alipaseinhibitorthat produces fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 12 publications
3
29
1
Order By: Relevance
“…Clearly, these findings might have been different if medications had not been adjusted in patients. Further studies using more sophisticated measures of cognitive function are needed to assess complaints of memory loss, which were reported by about 10% of persons treated in a large private practice setting (4). Patients in the present study also reported significant improvements in mood with weight loss, thus, confirming previous findings (33).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Clearly, these findings might have been different if medications had not been adjusted in patients. Further studies using more sophisticated measures of cognitive function are needed to assess complaints of memory loss, which were reported by about 10% of persons treated in a large private practice setting (4). Patients in the present study also reported significant improvements in mood with weight loss, thus, confirming previous findings (33).…”
Section: Discussionsupporting
confidence: 88%
“…Such studies should compare the results of brief, protocol-guided therapy not only with group behavior modification but also with treatment by pharmacotherapy alone, as is likely to be dispensed in busy primary care practices. We, like others (4,19,24,25,26), believe that the best results will be obtained when patients combine medication with their own efforts to modify eating and exercise habits. This belief is supported by the finding in the present study that the more food records patients completed during the first 18 weeks of treatment, the greater their short-and long-term weight losses.…”
Section: Discussionmentioning
confidence: 75%
“…As both norepinephrine and serotonin affect food behaviour, and as drugs acting on either norepinephrine or serotonin are available, the temptation was high to combine such compounds (especially phentermine fen¯uramine in the US and amfepramone fen¯uramine in some European countries such as Belgium) in order to improve the ef®cacy on weight loss or to minimize side effects by reducing the dosage of each anorectic agent. 16 The combination of phentermine and fen¯uramine has attracted considerable medical and media attention in the US since the publication of a long-term trial which suggested the ef®cacy and safety of such a combination, 17 and these results were con®rmed in another large study. 16 However, the recent publication pointing out the risk of severe valvular cardiac abnormalities with the combination phentermine ± fen¯uramine, 11 associated with the potential risk of pulmonary hypertension, 10 has recently thrown discredit on such a combined therapy.…”
Section: Serotoninergic Drugsmentioning
confidence: 99%
“…One must be cautioned not to extrapolate the data to longer periods as rates of compliance, pharmacological actions, metabolic benefits and safety remain to be evaluated. As recently stated (20) more research is needed to document long term efficacy of combined drug treatment of obesity, particularly the long-term safety of fluoxetine and dexfenfluramine and other combinations.…”
Section: Discussionmentioning
confidence: 99%